2021
DOI: 10.1021/acs.jpcb.1c01684
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics of Hemoglobin Reveals Structural Alterations and Explains the Interactions Driving Sickle Cell Fibrillation

Abstract: In sickle cell anemia, deoxyhemoglobin deforms RBCs by forming fibrils inside that disintegrate on oxygenation. We studied 100 ns long all-atom molecular dynamics (MD) for sickle and normal hemoglobin fibril models to understand this process, complemented by multiple 1 μs MD for a single tetramer of sickle and normal hemoglobin in deoxy and oxy states. We find that the presence of hydrophobic residues without a bulky side chain at β-6 in hemoglobin is the reason for the stability of the fibrils. Moreover, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…MD simulations of sickle and normal hemoglobin and hemoglobin fibril models were also recently reported [134][135][136] . Maity and Pal 135 argued that the presence of hydrophobic residues without a bulky side chain at β6 in hemoglobin explained the stability of the fibrils, consistent with the experiments by Adachi et al 137 , which showed that some substituents in the 6 position, such as phenylalanine and tryptophan, polymerized less readily compared to deoxy-HbS and that when oversaturated polymerization occurred without the delay time observed for HbS. Adachi et al argued that the difficulty of insertion of the bulky side chains of phenylalanine and tryptophan into the hydrophobic acceptor pocket on an adjacent tetramer could inhibit nuclei formation prior to polymerization.…”
Section: And Refs Therein)mentioning
confidence: 94%
“…MD simulations of sickle and normal hemoglobin and hemoglobin fibril models were also recently reported [134][135][136] . Maity and Pal 135 argued that the presence of hydrophobic residues without a bulky side chain at β6 in hemoglobin explained the stability of the fibrils, consistent with the experiments by Adachi et al 137 , which showed that some substituents in the 6 position, such as phenylalanine and tryptophan, polymerized less readily compared to deoxy-HbS and that when oversaturated polymerization occurred without the delay time observed for HbS. Adachi et al argued that the difficulty of insertion of the bulky side chains of phenylalanine and tryptophan into the hydrophobic acceptor pocket on an adjacent tetramer could inhibit nuclei formation prior to polymerization.…”
Section: And Refs Therein)mentioning
confidence: 94%
“…By plotting the cluster centers or representatives resulting from each method on the corresponding FEL, we can compare the degree to which a method captures the conformational space. It is important to note that we do not apply clustering to the FEL as done in other studies. , The evaluation of how well a clustering method performs is based on how well the resulting cluster centers cover the FEL minima and the states around and between minima, without populating the entire space, i.e., while still differentiating between the input conformations.…”
Section: Methodsmentioning
confidence: 99%
“…29 A single-point mutation (E6V) in the β chains of hemoglobin leads to sickle cell anemia. 30,31 This mutation causes the aggregation of hemoglobin fibrils in the absence of O 2 (T) that leads to the deformation of red blood cells; however, when O 2 is present (R), the fibrils disintegrate. 31,32 Having a means of characterizing the conformational landscape is crucial for identifying states for these more heterogeneous proteins/regions, which are essential for understanding enzymatic mechanisms or the effects of allosteric modulators and of disease-related mutations.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations